Les pays socialistes de l’Est et l’unité européenne – La tradition dans le socialisme et le socialisme dans la tradition : i. Le fédéralisme en Europe de l’Est. La perception et la politique régionale est-européenne de l’unité socialiste (1ère partie) - Pilisi, Paul (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1979)
Throughout the XIXth century federalism in Eastern Europe sought to regroup small nations and states within federal structures capable of guaranteeing their collective independence in the long-term vis-à-vis those powers directly interested in that region of the continent.After the First World War the federalist forces of Eastern Europe, conscious of the tragic effects of the balkanization of Central and Eastern Europe, had approached regional reconstruction in a spirit of unity. This unity, whose spirit and idea derived from a common historical experience, was taken up by the progressive forces active within the resistance during the Second World War.Shortly thereafter, among the political forces tending to promote regional unity, the socialist and communist parties engaged in activities of major importance. From their initial perspective, the solidarity of the Eastern Countries was to lead to the establishment of federal structures without the adhesion of the Soviet Union.